Pictorial Review of Imaging Spectrum of Epilepsy on Magnetic Resonance Imaging - Surla Harathi; A. Sravan Krishna Reddy; Pentyala Suneetha; J. Nanda Gopal (Asian Journal of Medical Radiological Research, 2021)
Background: Objectives: The objective of our study is to review different imaging spectrums of epilepsy on MRI. To diagnose structural abnormalities in the brain associated with the cause of seizures with MRI. Subjects and Methods : It is a hospital-based prospective observational study that was carried out in 80 patients with a history of epilepsy in Narayana medical college and general hospital, Nellore in   a period of 2 years from October 2019 to October 2021. All age group patients were included in the study without any gender predilection. Magnetic resonance imaging was performed on these patients and the results were recorded. Results: Out of these 80 patients, 30 patients (37.5%) had no abnormal neuroimaging findings. Most of the patients presented with generalized tonic-clonic seizures. The most common imaging findings were of cerebrovascular diseases (venous thrombosis/ infarct with gliosis) in about 16 cases (20%), developmental disorders in 17 cases (21.25%) of which mesial temporal sclerosis was the commonest (7 out of 17 cases), focal cortical dysplasia was seen in 3 cases. Other causes include infectious granulomas in 9 cases (11.25%) (tuberculomas and neurocysticercosis) and tumors in 2 cases (2.5%). vascular malformations (2 cases), and phakomatoses like tuberous sclerosis and Sturge weber syndrome (3 cases). Conclusion: MRI is a non-invasive modality with no radiation hazard and with its excellent gray-white matter resolution and multiplanar imaging capability helps in the detection of small and subtle lesions. With appropriate imaging protocol, our study observed that MR evaluation with increases sensitivity and specificity in the evaluation of seizures.